Acidified nitrite contributes to the antitumor effect of cold atmospheric plasma on melanoma cells - Zimmermann, Tom; Gebhardt, Lisa; Kreiß, Lucas; Schneider, Christin; Arndt, Stephanie; Karrer, Sigrid; Friedrich, Oliver; Fischer, Michael Jochen Marco; Boßerhoff, Anja Katrin (International Journal of Molecular Sciences, 2021)
Cold atmospheric plasma (CAP) is partially ionized gas near room temperature with previously reported antitumor effects. Despite extensive research and growing interest in this technol-ogy, active components and molecular mechanisms of CAP are not fully understood to date. We used Raman spectroscopy and colorimetric assays to determine elevated nitrite and nitrate levels after treatment with a MiniFlatPlaster CAP device. Previously, we demonstrated CAP-induced acidification. Cellular effects of nitrite and strong extracellular acidification were assessed using live-cell imaging of intracellular Ca2+ levels, cell viability analysis as well as quantification of p21 and DNA damage. We further characterized these observations by analyzing established molecular effects of CAP treatment. A synergistic effect of nitrite and acidification was found, leading to strong cytotoxicity in melanoma cells. Interestingly, protein nitration and membrane damage were absent after treatment with acidified nitrite, thereby challenging their contribution to CAP-induced cyto-toxicity. Further, phosphorylation of ERK1/2 was increased after treatment with both acidified ni-trite and indirect CAP. This study characterizes the impact of acidified nitrite on melanoma cells and supports the importance of RNS during CAP treatment. Further, it defines and evaluates im-portant molecular mechanisms that are involved in the cancer cell response to CAP.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Acidification; Acidified nitrite; Cold atmospheric plasma; Malignant melanoma; Membrane damage; Nitration; Nitrite

An advanced optical clearing protocol allows label-free detection of tissue necrosis via multiphoton microscopy in injured whole muscle - Schneidereit, Dominik; Broellochs, Anita; Ritter, Paul; Kreiß, Lucas; Mokhtari, Zeinab; Beilhack, Andreas; Krönke, Gerhard; Ackermann, Jochen; Faas, Maria; Grüneboom, Anika; Schürmann, Sebastian; Friedrich, Oliver (Theranostics, 2021)
Rationale: Structural remodeling or damage as a result of disease or injury is often not evenly distributed throughout a tissue but strongly depends on localization and extent of damaging stimuli. Skeletal muscle as a mechanically active organ can express signs of local or even systemic myopathic damage, necrosis, or repair. Conventionally, muscle biopsies (patients) or whole muscles (animal models) are mechanically sliced and stained to assess structural alterations histologically. Three-dimensional tissue information can be obtained by applying deep imaging modalities, e.g. multiphoton or light-sheet microscopy. Chemical clearing approaches reduce scattering, e.g. through matching refractive tissue indices, to overcome optical penetration depth limits in thick tissues.
CRIS-Team WoS Importer:2021-01-22

A novel modular opto-biomechatronics bioreactor for simultaneous isotropic mechanical stretch application and fluorescence microscopy under cell and tissue culture conditions - Merten, Anna-Lena; Schöler, Ulrike; Lesko, Christian; Kreiß, Lucas; Schneidereit, Dominik; Linsenmeier, Fabian; Stolz, Axel; Rappl, Sebastian; Ali, Mohamed; Potié, Tim; Ahmed, Adel; Morales-Dalmau, Jordi; et al. (Biosensors and Bioelectronics: X, 2024)
Mechanical stresses are an environmental challenge virtually all tissues in the body are exposed to and thus, are of fundamental interest to study cell reactions in mechanobiology. Yet, unlike acute short-term mechanical cell stimulations, long-term or cyclic mechano-stimulation as experienced in the body is difficult to reproduce. Bioreactors are designed to control cell culture conditions, but still, there are yet no technical solutions available to merge bioreactor and opto-biomechatronics technologies for cyclic stretch-applications and simultaneous live cell imaging. To close this gap, we have engineered an opto-biomechatronics module, consisting of our in-house developed IsoStretcher technology and customised epifluorescence optics, into an automated bioreactor platform. For this, redesigned polydimethylsiloxane (PDMS) chambers with closed geometry (∽700 μL internal volume) to warrant sterile operation were developed. Those chambers could be flushed with cell solution for cell seeding in a sterile manner. The epifluorescence imaging module was engineered into the reactor underneath the IsoStretcher to allow for continuous image acquisition during long-term stretch cycles (hours to days). The system was validated on human fibroblast BJ foreskin cells, and Cal-520 Ca2＋ fluorescence was stably imaged using our in-built autofocus functionality. Cultures for 24 h within the IsoStretcher-bioreactor preserved a normal cell morphology as compared to external incubator control cultures. Isotropic stretch was reliably transferred to the cell membranes. Our system with in-built bioreactor and opto-biomechatronics functionality provides a holistic technology platform for the growing field of mechanobiology to allow long-term observations of cultured single cells and confluent cell layers that are subjected to cyclic long-term isotropic stretch protocols.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Automation; Bioreactor; Cell stretching device; Mechanosensitive ion channels; Mechanotransduction

Anti-beta 7 integrin treatment impedes the recruitment on non-classical monocytes to the gut and delays macrophage-mediated intestinal wound healing - Sommer, Katrin; Heidbreder, Karin; Kreiß, Lucas; Dedden, Mark; Paap, Eva-Maria; Wiendl, Maximilian; Becker, Emily; Atreya, Raja; Müller, Tanja; Atreya, Imke; Waldner, Maximilian; Schürmann, Sebastian; et al. (Clinical and Translational Medicine, 2023)
BackgroundClosing mucosal defects to reach mucosal healing is an important goal of therapy in inflammatory bowel disease (IBD). Among other cells, monocyte-derived macrophages are centrally involved in such intestinal wound healing. We had previously demonstrated that the anti-alpha 4 beta 7 integrin antibody vedolizumab blocks the recruitment of non-classical monocytes as biased progenitors of wound healing macrophages to the gut and delays wound healing. However, although important for the interpretation of disappointing results in recent phase III trials in IBD, the effects of the anti-beta 7 antibody etrolizumab on wound healing are unclear so far. MethodsWe analyzed the expression of etrolizumab targets on human and mouse monocyte subsets by flow cytometry and assessed their function in adhesion and homing assays. We explored wound-associated monocyte recruitment dynamics with multi-photon microscopy and compared the effects of etrolizumab and vedolizumab surrogate (-s) antibodies on experimental wound healing and wound-associated macrophage abundance. Finally, we investigated wound healing macrophage signatures in the large intestinal transcriptome of patients with Crohn's disease treated with etrolizumab. ResultsHuman and mouse non-classical monocytes expressed more alpha E beta 7 integrin than classical monocytes and were a target of etrolizumab-s, which blocked non-classical monocyte adhesion to MAdCAM-1 and E-Cadherin as well as gut homing in vivo. Intestinal wound healing was delayed on treatment with etrolizumab-s along with a reduction of peri-lesional wound healing macrophages. Wound healing macrophage signatures in the colon of patients with Crohn's disease were substantially down-regulated on treatment with etrolizumab, but not with placebo. ConclusionsCombined blockade of alpha E beta 7 and alpha 4 beta 7 with etrolizumab seems to exceed the effect of anti-alpha 4 beta 7 treatment on intestinal wound healing, which might help to inform further investigations to understand the recent observations in the etrolizumab phase III trial program.
CRIS-Team WoS Importer:2023-05-05

ATP citrate lyase (ACLY)-dependent immunometabolism in mucosal T cells drives experimental colitis in vivo - Schulz-Kuhnt, Anja; Rühle, Katharina; Javidmehr, Asal; Döbrönti, Michael; Biwank, Jana; Knittel, Selina; Neidlinger, Peter; Leupold, Jannik; Liu, Lijuan; Dedden, Mark; Taudte, Regina Verena; Geßner, Arne; et al. (Gut, 2024)
Objective Mucosal T cells play a major role in inflammatory bowel disease (IBD). However, their immunometabolism during intestinal inflammation is poorly understood. Due to its impact on cellular metabolism and proinflammatory immune cell function, we here focus on the enzyme ATP citrate lyase (ACLY) in mucosal T cell immunometabolism and its relevance for IBD. Design ACLY expression and its immunometabolic impact on colitogenic T cell function were analysed in mucosal T cells from patients with IBD and in two experimental colitis models. Results ACLY was markedly expressed in colon tissue under steady-state conditions but was significantly downregulated in lamina propria mononuclear cells in experimental dextran sodium sulfate-induced colitis and in CD4+ and to a lesser extent in CD8+ T cells infiltrating the inflamed gut in patients with IBD. ACLY-deficient CD4+ T cells showed an impaired capacity to induce intestinal inflammation in a transfer colitis model as compared with wild-type T cells. Assessment of T cell immunometabolism revealed that ACLY deficiency dampened the production of IBD-relevant cytokines and impaired glycolytic ATP production but enriched metabolites involved in the biosynthesis of phospholipids and phosphatidylcholine. Interestingly, the short-chain fatty acid butyrate was identified as a potent suppressor of ACLY expression in T cells, while IL-36α and resolvin E1 induced ACLY levels. In a translational approach, in vivo administration of the butyrate prodrug tributyrin downregulated mucosal infiltration of ACLYhigh CD4+ T cells and ameliorated chronic colitis. Conclusion ACLY controls mucosal T cell immunometabolism and experimental colitis. Therapeutic modulation of ACLY expression in T cells emerges as a novel strategy to promote the resolution of intestinal inflammatio

CAS3D: 3D quantitative morphometry on Second Harmonic Generation image volumes from single skeletal muscle fibers - Schneidereit, Dominik; Bauer, Julian; Mnuskina, Sofia; Nübler, Stefanie; Cacciani, Nicola; Mühlberg, Alexander; Kreiß, Lucas; Ritter, Paul; Schürmann, Sebastian; Larsson, Lars; Friedrich, Oliver (Computers in Biology and Medicine, 2024)
The CAS3D image processing method intuitively applies a combination of Fourier space and real space 3D analysis algorithms to volumetric images of single skeletal muscle fiber Myosin II Second Harmonic Generation (SHG) XYZ image data. Our developed tool automatically quantifies the myofibrillar orientation in muscle samples by determining the cosine angle sum of intensity gradients in 3D (CAS3D) while determining the mean sarcomere length (SL) and sample orientation. The expected CAS3D values could be reproduced from ideal artificial data sets. Applied random noise in artificial images lowers the detected CAS3D value, and for noise levels below 20%, the correlation can be approximated by a linear function with a slope of −0.006 CAS3D/noise%. The deviations in SL and orientation detection were determined on ideal and noisy artificial data sets and were statistically indistinguishable from 0 (null hypothesis t-test P > 0.1). The software was applied to a previously published data set of single skeletal muscle fiber volumetric SHG image data from a rat intensive care unit (ICU) model of ventilator-induced diaphragm dysfunction (VIDD) with treatment regimens involving the small anti-inflammatory molecules BGP-15, vamorolone, or prednisolone. Our method reliably reproduced the results of the previous work and improved the standard deviation of the cosine angle sum detection in all sample groups from a mean of 0.03 to 0.008. This improvement is achieved by applying analysis algorithms to the whole volumetric images in 3D in contrast to the previously common method of slice-wise XY analysis.
CRIS-Team Scopus Importer:2024-07-19
Keywords: 3D image analysis; Quantitative morphometry; Second harmonic generation; Skeletal muscle; Software automation

Diffuse reflectance spectroscopy and Raman spectroscopy for label-free molecular characterization and automated detection of human cartilage and subchondral bone - Kreiß, Lucas; Hohmann, Martin; Klämpfl, Florian; Schürmann, Sebastian; Dehghani, Faramarz; Schmidt, Michael; Friedrich, Oliver; Büchler, Lorenz (Sensors and Actuators B-Chemical, 2019)
Optical technologies hold potential for bio-medical research as well as the clinical routine, since they allow contact-free, non-destructive access to several clinically relevant features of tissues. In this study, diffuse reflectance spectroscopy and spontaneous Raman spectroscopy have been applied to human hip samples in order to characterize differences between cartilage and adjacent subchondral bone tissue. Mathematical decomposition of absorption and scattering properties is an important aspect in diffuse reflectance data analysis. Here, we present the novel application of Bayesian statistics to this analysis, which can extract probability density spectra of the absorption coefficient and the scattering coefficient. Using this concept of a Bayesian decomposition algorithm for the spectral decomposition, it was possible to find characteristic differences in the relative concentration of melanin and haemoglobin as well as in scattering properties. Furthermore, this allowed a reconstruction of probability density plots for scattering coefficient and absorption coefficient instead of singular values. Complemented by the results of Raman spectroscopy, it was further possible to detect significant differences in the ratio of minerals (such as hydroxyl apatite) to bio-molecules (such as proteins) when comparing bony tissue regions to the surrounding cartilage. Finally, it was possible to use these molecular contrast mechanisms for highly-accurate, automated tissue classification using machine learning algorithms on the level of individual patients.
CRIS-Team Scopus Importer:2019-10-04
Keywords: Bayesian inference; Bone; Cartilage; Diffuse reflectance spectroscopy; Label-free; Machine learning; Raman spectroscopy

High-throughput imaging across multiple spatial scales with the multi-camera array microscope (MCAM) - Kreiß, Lucas; Zhou, Kevin; Kim, Kanghyun; Harfouche, Mark; Xu, Shiqi; Jönsson, Joakim; Lee, Kyung Chul; Cook, Clare; Yang, Xi; Reamey, Paul; Saliu, Veton; Horstmeyer, Gregor; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2023)
“Anyone who uses a microscope has likely noticed the limitation of the trade-off between the field of view and the resolution”.1 To acquire highly resolved images at large fields of view, existing techniques typically record sequential images at different positions and then digitally stitch composite images. There are alternatives to this mechanical scanning procedure, such as structured illumination microscopy2 or Fourier ptychography3,4 that record sequential images at varying illuminations prevent mechanical scanning for high-resolution image composites. However, all of these approaches require sequential images and thus compromise speed, temporal resolution and experimental throughput. Here we present the Multi-Camera Array Microscope (MCAM), which is a microscope system that utilizes an array of many synchronized cameras, each with an individual imaging lens, for simultaneous image capture. The MCAM enables enhanced imaging capabilities and novel applications in various scientific and medical fields, by combining the images acquired from each individual camera-lens pair.
CRIS-Team Scopus Importer:2023-10-13

Imaging Dynamics Beneath Turbid Media via Parallelized Single-Photon Detection - Xu, Shiqi; Yang, Xi; Liu, Wenhui; Jonsson, Joakim; Qian, Ruobing; Konda, Pavan Chandra; Zhou, Kevin C.; Kreiß, Lucas; Wang, Haoqian; Dai, Qionghai; Berrocal, Edouard; Horstmeyer, Roarke (Advanced Science, 2022)
Noninvasive optical imaging through dynamic scattering media has numerous important biomedical applications but still remains a challenging task. While standard diffuse imaging methods measure optical absorption or fluorescent emission, it is also well-established that the temporal correlation of scattered coherent light diffuses through tissue much like optical intensity. Few works to date, however, have aimed to experimentally measure and process such temporal correlation data to demonstrate deep-tissue video reconstruction of decorrelation dynamics. In this work, a single-photon avalanche diode array camera is utilized to simultaneously monitor the temporal dynamics of speckle fluctuations at the single-photon level from 12 different phantom tissue surface locations delivered via a customized fiber bundle array. Then a deep neural network is applied to convert the acquired single-photon measurements into video of scattering dynamics beneath rapidly decorrelating tissue phantoms. The ability to reconstruct images of transient (0.1-0.4 s) dynamic events occurring up to 8 mm beneath a decorrelating tissue phantom with millimeter-scale resolution is demonstrated, and it is highlighted how the model can flexibly extend to monitor flow speed within buried phantom vessels.
CRIS-Team WoS Importer:2022-07-08

Interferon regulatory factor 1 (IRF-1) promotes intestinal group 3 innate lymphoid responses during Citrobacter rodentium infection - Schmalzl, Angelika; Leupold, Tamara; Kreiß, Lucas; Waldner, Maximilian; Schürmann, Sebastian; Neurath, Markus; Becker, Christoph; Wirtz, Stefan (Nature Communications, 2022)
Group 3 innate lymphoid cells (ILC3s) are crucial mediators of immunity and epithelial barrier function during immune responses against extracellular bacteria. Here, we identify Interferon regulatory factor 1 (IRF-1), a transcription factor previously associated with type 1 immunity, as an essential regulator of intestinal ILC3 accumulation and effector cytokine production. We demonstrate that IRF-1 is upregulated in the context of infection with the enteropathogen Citrobacter rodentium and that its presence is central for anatomical containment and prevention of pathogen dissemination. We furthermore show that IRF-1 is required in order for intestinal ILC3s to produce large amounts of the protective effector cytokine IL-22 early in the course of infection. On a molecular level, our data indicate that IRF-1 controls ILC3 numbers and their activation by direct transcriptional regulation of the IL-12Rβ1 chain, thereby allowing ILCs to physiologically respond to IL-23 stimulation.
CRIS-Team Scopus Importer:2022-10-14

Label-free analysis of experimental lung fibrosis using multiphoton microscopy and Raman spectroscopy - Ganzleben, Ingo; Kreiß, Lucas; Mühlberg, Alexander; Friedrich, Oliver; Neurath, Markus; Schürmann, Sebastian; Waldner, Maximilian (EUROPEAN RESPIRATORY JOURNAL, 2021)
CRIS-Team WoS Importer:2022-02-25

Label-free analysis of inflammatory tissue remodeling in murine lung tissue based on multiphoton microscopy, Raman spectroscopy and machine learning - Kreiß, Lucas; Ganzleben, Ingo; Mühlberg, Alexander; Ritter, Paul; Schneidereit, Dominik; Becker, Christoph; Neurath, Markus; Friedrich, Oliver; Schürmann, Sebastian; Waldner, Maximilian (Journal of Biophotonics, 2022)
Inflammatory fibrotic tissue remodeling can lead to severe morbidity. Histopathology grading requires extraction of biopsies and elaborate tissue processing. Label-free optical technologies can provide diagnostic readout without preparation and artificial stainings and show potential for in vivo applications. Here, we present an integration of Raman spectroscopy (RS) and multiphoton microscopy for joint investigation of the bio-chemical composition and morphological features related to cellular components and connective tissue. Both modalities show that collagen signatures were significantly increased in a murine fibrosis model. Furthermore, autofluorescence signatures assigned to immune cells show high correlation with disease severity. RS indicates increased levels of elastin and lipids. Further, we investigated the effect of joint data sets on prediction performance in machine learning models. Although binary classification did not benefit from adding more features, multi-class classification was improved by integrated data sets.
CRIS-Team WoS Importer:2022-07-08

Label-Free Characterization and Quantification of Mucosal Inflammation in Common Murine Colitis Models With Multiphoton Imaging - Kreiß, Lucas; Thoma, Oana-Maria; Lemire, Sarah; Lechner, Kristina; Carlé, Birgitta-Elisabeth; Dilipkumar, Ashwathama; Kunert, Timo; Scheibe, Kristina; Heichler, Christina; Merten, Anna-Lena; Weigmann, Benno; Neufert, Clemens; et al. (Inflammatory Bowel Diseases, 2022)
Background Clinical challenges in inflammatory bowel diseases require microscopic in vivo evaluation of inflammation. Here, label-free imaging holds great potential, and recently, our group demonstrated the advantage of using in vivo multiphoton endomicroscopy for longitudinal animal studies. This article extends our previous work by in-depth analysis of label-free tissue features in common colitis models quantified by the multiphoton colitis score (MCS). Methods Fresh mucosal tissues were evaluated from acute and chronic dextran sulfate sodium (DSS), TNBS, oxazolone, and transfer colitis. Label-free imaging was performed by using second harmonic generation and natural autofluorescence. Morphological changes in mucosal crypts, collagen fibers, and cellularity in the stroma were analyzed and graded. Results Our approach discriminated between healthy (mean MCS = 2.5) and inflamed tissue (mean MCS > 5) in all models, and the MCS was validated by hematoxylin and eosin scoring of the same samples (85.2% agreement). Moreover, specific characteristics of each phenotype were identified. While TNBS, oxazolone, and transfer colitis showed high cellularity in stroma, epithelial damage seemed specific for chronic, acute DSS and transfer colitis. Crypt deformations were mostly observed in acute DSS. Conclusions Quantification of label-free imaging is promising for in vivo endoscopy. In the future, this could be valuable for monitoring of inflammatory pathways in murine models, which is highly relevant for the development of new inflammatory bowel disease therapeutics.
CRIS-Team WoS Importer:2022-10-07

Label-Free In Vivo Histopathology of Experimental Colitis via 3-Channel Multiphoton Endomicroscopy - Kreiß, Lucas; Thoma, Oana Maria; Dilipkumar, Ashwathama; Carlé, Birgitta-Elisabeth; Longequeue, Pascal; Kunert, Timo; Rath, Timo; Hildner, Kai; Neufert, Clemens; Neurath, Markus; Friedrich, Oliver; Schürmann, Sebastian; et al. (Gastroenterology, 2020)
CRIS-Team Scopus Importer:2020-08-28

Label-Free Multiphoton Endomicroscopy for Minimally Invasive In Vivo Imaging - Dilipkumar, Ashwathama; Al-Shemmary, Alaa; Kreiß, Lucas; Cvecek, Kristian; Carlé, Birgitta-Elisabeth; Knieling, Ferdinand; Menezes, Jean Gonzales; Thoma, Oana-Maria; Schmidt, Michael; Neurath, Markus; Waldner, Maximilian; Friedrich, Oliver; et al. (Advanced Science, 2019)
Multiphoton microscopy of cellular autofluorescence and second harmonic generation from collagen facilitates imaging of living cells and tissues without the need for additional fluorescent labels. Here, a compact multiphoton endomicroscope for label-free in vivo imaging in small animals via side-viewing needle objectives is presented. Minimal invasive imaging at cellular resolution is performed in colonoscopy of mice without surgical measures and without fluorescent dyes as a contrast agent. The colon mucosa is imaged repeatedly in the same animal in a mouse model of acute intestinal inflammation to study the process of inflammation at the tissue level within a time period of ten days, demonstrating the capabilities of label-free endomicroscopy for longitudinal studies for the first time.
CRIS-Team Scopus Importer:2019-05-02
Keywords: endoscopy; inflammatory bowel disease; multiphoton microscopy; optical imaging

Multiphoton Microscopy Reveals DAPK1‐Dependent Extracellular Matrix Remodeling in a Chorioallantoic Membrane (CAM) Model - Kunze, Philipp; Kreiß, Lucas; Novosadová, Vendula; Roehe, Adriana V.; Steinmann, Sara; Prochazka, Jan; Geppert, Carol-Immanuel; Hartmann, Arndt; Schürmann, Sebastian; Friedrich, Oliver; Schneider-Stock, Regine (Cancers, 2022)
Cancer cells facilitate tumor growth by creating favorable tumor micro‐environments (TME), altering homeostasis and immune response in the extracellular matrix (ECM) of surrounding tissue. A potential factor that contributes to TME generation and ECM remodeling is the cytoskeleton‐associated human death‐associated protein kinase 1 (DAPK1). Increased tumor cell motility and de‐adhesion (thus, promoting metastasis), as well as upregulated plasminogen-signaling, are shown when functionally analyzing the DAPK1 ko‐related proteome. However, the systematic investigation of how tumor cells actively modulate the ECM at the tissue level is experimentally challenging since animal models do not allow direct experimental access while artificial in vitro scaffolds cannot simulate the entire complexity of tissue systems. Here, we used the chorioallantoic membrane (CAM) assay as a natural, collagen‐rich tissue model in combination with all‐optical experimental access by multiphoton microscopy (MPM) to study the ECM remodeling potential of colorectal tumor cells with and without DAPK1 in situ and even in vivo. This approach demonstrates the suitability of the CAM assay in combination with multiphoton microscopy for studying collagen remodeling during tumor growth. Our results indicate the high ECM remodeling potential of DAPK1 ko tumor cells at the tissue level and support our findings from proteomics.
CRIS-Team Scopus Importer:2022-05-20
Keywords: collagen; colon cancer; ECM remodeling; MPM; uPAR

Myofibrillar Lattice Remodeling Is a Structural Cytoskeletal Predictor of Diaphragm Muscle Weakness in a Fibrotic mdx (mdx Cmah(-/-)) Model - Ritter, Paul; Nübler, Stefanie; Buttgereit, Andreas; Smith, Lucas R.; Mühlberg, Alexander; Bauer, Julian; Michael, Mena; Kreiß, Lucas; Haug, Michael; Barton, Elisabeth; Friedrich, Oliver (International Journal of Molecular Sciences, 2022)
Duchenne muscular dystrophy (DMD) is a degenerative genetic myopathy characterized by complete absence of dystrophin. Although the mdx mouse lacks dystrophin, its phenotype is milder compared to DMD patients. The incorporation of a null mutation in the Cmah gene led to a more DMD-like phenotype (i.e., more fibrosis). Although fibrosis is thought to be the major determinant of 'structural weakness', intracellular remodeling of myofibrillar geometry was shown to be a major cellular determinant thereof. To dissect the respective contribution to muscle weakness, we assessed biomechanics and extra- and intracellular architecture of whole muscle and single fibers from extensor digitorum longus (EDL) and diaphragm. Despite increased collagen contents in both muscles, passive stiffness in mdx Cmah(-/-) diaphragm was similar to wt mice (EDL muscles were twice as stiff). Isometric twitch and tetanic stresses were 50% reduced in mdx Cmah(-/-) diaphragm (15% in EDL). Myofibrillar architecture was severely compromised in mdx Cmah(-/-) single fibers of both muscle types, but more pronounced in diaphragm. Our results show that the mdx Cmah(-/-) genotype reproduces DMD-like fibrosis but is not associated with changes in passive visco-elastic muscle stiffness. Furthermore, detriments in active isometric force are compatible with the pronounced myofibrillar disarray of the dystrophic background.
CRIS-Team WoS Importer:2022-09-30

Natural NADH and FAD Autofluorescence as Label-Free Biomarkers for Discriminating Subtypes and Functional States of Immune Cells - Lemire, Sarah; Thoma, Oana-Maria; Kreiß, Lucas; Völkl, Simon; Friedrich, Oliver; Neurath, Markus; Schürmann, Sebastian; Waldner, Maximilian (International Journal of Molecular Sciences, 2022)
Immune cell activity is a major factor for disease progression in inflammatory bowel diseases (IBD). Classifying the type and functional state of immune cells is therefore crucial in clinical diagnostics of IBD. Label-free optical technologies exploiting NADH and FAD autofluorescence, such as multiphoton microscopy, have been used to describe tissue morphology in healthy and inflamed colon samples. Nevertheless, a strategy for the identification of single immune cell subtypes within the tissue is yet to be developed. This work aims to initiate an understanding of autofluorescence changes depending on immune cell type and activation state. For this, NADH and FAD autofluorescence signals of different murine immune cell subtypes under native conditions, as well as upon in vitro stimulation and cell death, have been evaluated. Autofluorescence was assessed using flow cytometry and multiphoton microscopy. Our results reveal significantly increased NADH and FAD signals in innate immune cells compared to adaptive immune cells. This allowed identification of relative amounts of neutrophils and CD4+ T cells in mixed cell suspensions, by using NADH signals as a differentiation marker. Furthermore, in vitro stimulation significantly increased NADH and FAD autofluorescence in adaptive immune cells and macrophages. Cell death induced a significant drop in NADH autofluorescence, while FAD signals were hardly affected. Taken together, these results demonstrate the value of autofluorescence as a tool to characterize immune cells in different functional states, paving the way to the label-free clinical classification of IBD in the future.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Cell autofluorescence; FAD; Flow cytometry; Immune cells; Inflammatory bowel diseases; Multiphoton microscopy; NADH

SEMPAI: a Self-Enhancing Multi-Photon Artificial Intelligence for Prior-Informed Assessment of Muscle Function and Pathology - Mühlberg, Alexander; Ritter, Paul; Langer, Sabine; Goossens, Chloë; Nübler, Stefanie; Schneidereit, Dominik; Taubmann, Oliver; Denzinger, Felix; Nörenberg, Dominik; Haug, Michael; Schürmann, Sebastian; Horstmeyer, Roarke; et al. (Advanced Science, 2023)
Deep learning (DL) shows notable success in biomedical studies. However, most DL algorithms work as black boxes, exclude biomedical experts, and need extensive data. This is especially problematic for fundamental research in the laboratory, where often only small and sparse data are available and the objective is knowledge discovery rather than automation. Furthermore, basic research is usually hypothesis-driven and extensive prior knowledge (priors) exists. To address this, the Self-Enhancing Multi-Photon Artificial Intelligence (SEMPAI) that is designed for multiphoton microscopy (MPM)-based laboratory research is presented. It utilizes meta-learning to optimize prior (and hypothesis) integration, data representation, and neural network architecture simultaneously. By this, the method allows hypothesis testing with DL and provides interpretable feedback about the origin of biological information in 3D images. SEMPAI performs multi-task learning of several related tasks to enable prediction for small datasets. SEMPAI is applied on an extensive MPM database of single muscle fibers from a decade of experiments, resulting in the largest joint analysis of pathologies and function for single muscle fibers to date. It outperforms state-of-the-art biomarkers in six of seven prediction tasks, including those with scarce data. SEMPAI's DL models with integrated priors are superior to those without priors and to prior-only approaches.
CRIS-Team Scopus Importer:2023-08-25
Keywords: deep learning; explainable artificial intelligence; meta-learning; multiphoton microscopy; muscle research; prior information integration; scientific machine learning

Tensorial tomographic Fourier ptychography with applications to muscle tissue imaging - Xu, Shiqi; Yang, Xi; Ritter, Paul; Dai, Xiang; Lee, Kyung Chul; Kreiß, Lucas; Zhou, Kevin C.; Kim, Kanghyun; Chaware, Amey; Neff, Jadee; Glass, Carolyn; Lee, Seung Ah; et al. (Advanced Photonics, 2024)
We report tensorial tomographic Fourier ptychography (T2oFu), a nonscanning label-free tomographic microscopy method for simultaneous imaging of quantitative phase and anisotropic specimen information in 3D. Built upon Fourier ptychography, a quantitative phase imaging technique, T2oFu additionally highlights the vectorial nature of light. The imaging setup consists of a standard microscope equipped with an LED matrix, a polarization generator, and a polarization-sensitive camera. Permittivity tensors of anisotropic samples are computationally recovered from polarized intensity measurements across three dimensions. We demonstrate T2oFu’s efficiency through volumetric reconstructions of refractive index, birefringence, and orientation for various validation samples, as well as tissue samples from muscle fibers and diseased heart tissue. Our reconstructions of healthy muscle fibers reveal their 3D fine-filament structures with consistent orientations. Additionally, we demonstrate reconstructions of a heart tissue sample that carries important polarization information for detecting cardiac amyloidosis.
CRIS-Team Scopus Importer:2024-05-24
Keywords: computational imaging; label-free imaging; phase retrieval microscopy; polarization-sensitive imaging; three-dimensional imaging

Transient Motion Classification Through Turbid Volumes via Parallelized Single-Photon Detection and Deep Contrastive Embedding - Xu, Shiqi; Liu, Wenhui; Yang, Xi; Jönsson, Joakim; Qian, Ruobing; McKee, Paul; Kim, Kanghyun; Konda, Pavan Chandra; Zhou, Kevin C.; Kreiß, Lucas; Wang, Haoqian; Berrocal, Edouard; et al. (Frontiers in Neuroscience, 2022)
Fast noninvasive probing of spatially varying decorrelating events, such as cerebral blood flow beneath the human skull, is an essential task in various scientific and clinical settings. One of the primary optical techniques used is diffuse correlation spectroscopy (DCS), whose classical implementation uses a single or few single-photon detectors, resulting in poor spatial localization accuracy and relatively low temporal resolution. Here, we propose a technique termed Classifying Rapid decorrelation Events via Parallelized single photon dEtection (CREPE), a new form of DCS that can probe and classify different decorrelating movements hidden underneath turbid volume with high sensitivity using parallelized speckle detection from a 32 × 32 pixel SPAD array. We evaluate our setup by classifying different spatiotemporal-decorrelating patterns hidden beneath a 5 mm tissue-like phantom made with rapidly decorrelating dynamic scattering media. Twelve multi-mode fibers are used to collect scattered light from different positions on the surface of the tissue phantom. To validate our setup, we generate perturbed decorrelation patterns by both a digital micromirror device (DMD) modulated at multi-kilo-hertz rates, as well as a vessel phantom containing flowing fluid. Along with a deep contrastive learning algorithm that outperforms classic unsupervised learning methods, we demonstrate our approach can accurately detect and classify different transient decorrelation events (happening in 0.1–0.4 s) underneath turbid scattering media, without any data labeling. This has the potential to be applied to non-invasively monitor deep tissue motion patterns, for example identifying normal or abnormal cerebral blood flow events, at multi-Hertz rates within a compact and static detection probe.
CRIS-Team Scopus Importer:2022-08-05
Keywords: contrastive learning; diffuse correlation; multimode fiber; neurobehavior; self-supervised learning; SPAD array; zero-shot learning